2020
DOI: 10.2147/ppa.s258292
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adherence to Anti-Tuberculosis Treatment Among Pediatric Patients at Nekemte Specialized Hospital, Western Ethiopia</p>

Abstract: Background Non-adherence to tuberculosis treatment is the most challenging and hindering factor for successful tuberculosis therapy. The long duration of tuberculosis treatment and the undesirable effects of anti-tuberculosis drugs result in non-adherence to treatment among pediatric patients. Hence, this study was aimed to evaluate pediatrics adherence status among tuberculosis pediatric patients on anti-tuberculosis treatment at Nekemte Specialized Hospital. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Similar findings were seen in study done by did not experience side effect were significant predictors. 5 Similar findings were seen in study done by Bagchi et al 6 In another study done by Santos et al showed that the majority of patients were compliant (63.9%). 7 Noncompliance was found in 36.1%.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were seen in study done by did not experience side effect were significant predictors. 5 Similar findings were seen in study done by Bagchi et al 6 In another study done by Santos et al showed that the majority of patients were compliant (63.9%). 7 Noncompliance was found in 36.1%.…”
Section: Discussionsupporting
confidence: 84%
“…Health education should be age-specific, gender-sensitive, delivered in the patient’s own language and address potential challenges for the caregiver when administering medication. 77 80 Health education is essential for PTB treatment adherence and for ensuring safety by improving patients’ understanding of risks and benefits and providing clear instructions for reporting adherence challenges and adverse events, thereby motivating treatment completion. 72 Patients need to know when to contact the healthcare provider in the event of symptoms suggestive of adverse effects.…”
Section: Standardmentioning
confidence: 99%
“…Pengetahuan yang dimiliki pasien menjadi salah satu faktor yang dapat mempengaruhi terjadinya kegagalan terapi selain peran pengawas minum obat, dukungan keluarga, akses transportasi dan jarak dari tempat tinggal pasien menuju tempat pelayanan kesehatan, motivasi dan efek samping yang dirasakan 3,4 . Kepatuhan diartikan sebagai tingkatan seseorang dalam berperilaku untuk memperoleh keberhasilan pengobatan, diet dan melakukan gaya hidup yang sesuai dengan rekomendasi dari pelayanan kesehatan 5,6 . Kepatuhan merupakan suatu gambaran perilaku yang terbentuk karena adanya interaksi dari petugas kesehatan dengan penerima terapi atau pasien agar pasien dapat mengerti rencana dan konsekuensi dari langkah yang diambil serta menyetujui hasil perencanaan dan melaksanakannya 7,8 .…”
Section: Tuberkulosis (Tb) Merupakan Penyakit Menular Yang Disebabkan...unclassified